2012
DOI: 10.1002/sia.4968
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a combined thermal treatment of substrate heating and post‐annealing on the microstructure of InGaZnO films and the device performance of their thin film transistors

Abstract: This study examined the possibility of engineering the microstructure of InGaZnO films and enhancing the device performance of their thin film transistors by combining the thermal treatments of substrate heating and post‐annealing. Microstructure characterization using high‐resolution transmission electron microscopy and energy‐filtered selected area electron diffraction helped us to unravel a systematic improvement in atomic order induced by substrate heating. Hall measurement analysis confirmed that the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Many reports have announced that the annealing process is dispensable for improving the electrical property of various FETs using original IV semiconductors [29], oxide semiconductors [30,31], layered semiconductors [32-34], etc. In the case of 4H-SiC included in the original IV, the annealing process created a passivation layer at the interface, and device parameters were improved, such as the electron mobility and subthreshold swing (SS).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have announced that the annealing process is dispensable for improving the electrical property of various FETs using original IV semiconductors [29], oxide semiconductors [30,31], layered semiconductors [32-34], etc. In the case of 4H-SiC included in the original IV, the annealing process created a passivation layer at the interface, and device parameters were improved, such as the electron mobility and subthreshold swing (SS).…”
Section: Introductionmentioning
confidence: 99%
“…If we could reduce the trap density of electron and improve the atomic arrangement, we could increase the carrier concentration. Therefore, the increase of carrier concentration by post-annealing is closely associated with improvement of atomic arrangement 29) . From these results, it is concluded that as the annealing temperature increased to 600 o C, the electrical properties was improved, but at 700 o C, a considerable diffusion occurred, leading to the structural rearrangement.…”
Section: Resultsmentioning
confidence: 99%